2018
DOI: 10.1016/j.scitotenv.2017.12.262
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle environmental evaluation of kettles: Recommendations for the development of eco-design regulations in the European Union

Abstract: Between 117 and 200 million kettles are used in the European Union (EU) every year. However, the full environmental impacts of kettles remain largely unknown. This paper presents a comprehensive life cycle assessment of conventional plastic and metallic kettles in comparison with eco-kettles. The results show that the use stage contributes 80% to the impacts. For this reason, the eco-kettle has over 30% lower environmental impacts due to a greater water efficiency and related lower energy consumption. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Unaccounted sources of MP release from other PP products involved in formula preparation can also contribute to MP exposure. For example, electrical kettles used to heat water for formula preparation are commonly PPbased and account for 60% 32 and 91% (data mining from Amazon UK) of the EU and UK kettle markets, respectively. Tests involving 3 kettles from different manufacturers in the UK (Supplementary Figure 1a), revealed that over 10 million PP-MPs per litre are released into the water during a single boil, which is in line with previous findings 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Unaccounted sources of MP release from other PP products involved in formula preparation can also contribute to MP exposure. For example, electrical kettles used to heat water for formula preparation are commonly PPbased and account for 60% 32 and 91% (data mining from Amazon UK) of the EU and UK kettle markets, respectively. Tests involving 3 kettles from different manufacturers in the UK (Supplementary Figure 1a), revealed that over 10 million PP-MPs per litre are released into the water during a single boil, which is in line with previous findings 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these models support environmental evaluation of appliances, thus enabling recommendations for the development of eco-design regulations in the EU, e.g., see [46].…”
Section: Discussionmentioning
confidence: 99%
“…Europe, with swift urbanization and industrialization, is now facing adverse challenges and pressures on consumption of energy, the emissions reduction and environmental pollution prevention (Stergiou & Kounetas, 2021). Europe had considered this thing long ago that, if the renovation of human society since the industrial rebellion were to be summarized in three words, then those should be urbanization, industrialization, and globalization (Gallego-Schmid et al, 2018). These three dimensions are in close relations with each other (Ciscar et al, 2011), but there is another factor which was ignored for several years, and that is environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%